2014
DOI: 10.1097/qai.0000000000000281
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Preterm Birth Among HIV-Infected Pregnant Ugandan Women Randomized to Lopinavir/Ritonavir- or Efavirenz-Based Antiretroviral Therapy

Abstract: Background Protease inhibitor-based antiretroviral therapy (ART) has been associated with preterm birth in some studies. We examined risk factors for preterm birth among women randomized to lopinavir/ritonavir- or efavirenz-based ART. Methods This was a planned secondary analysis of the PROMOTE-Pregnant Women and Infants Study, an open-label, randomized controlled trial comparing the risk of placental malaria among HIV-infected, ART-naïve pregnant Ugandan women assigned to initiate lopinavir/ritonavir- or ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 36 publications
3
37
2
Order By: Relevance
“…EFV-based regimens have demonstrated a null or protective relationship with preterm birth when compared to nevirapine-or dolutegravir-based regimens [49][50][51][52][53] and are widely available. Among infants in our study, birth outcomes were comparable to or more favourable than results from other sub-Saharan African countries for both preterm birth [52,[54][55][56][57] and low birth weight [55,56,58]. We did not observe pregnancy outcomes for women lost to follow-up, so our results may underestimate adverse birth outcomes and MTCT events.…”
Section: Discussionsupporting
confidence: 61%
“…EFV-based regimens have demonstrated a null or protective relationship with preterm birth when compared to nevirapine-or dolutegravir-based regimens [49][50][51][52][53] and are widely available. Among infants in our study, birth outcomes were comparable to or more favourable than results from other sub-Saharan African countries for both preterm birth [52,[54][55][56][57] and low birth weight [55,56,58]. We did not observe pregnancy outcomes for women lost to follow-up, so our results may underestimate adverse birth outcomes and MTCT events.…”
Section: Discussionsupporting
confidence: 61%
“…There were no differences between study arms in the numbers of stillbirths, preterm deliveries, low birth weight infants, or neonatal deaths. [15, 20]…”
Section: Resultsmentioning
confidence: 99%
“…95 In contrast, a secondary analysis of the Pregnant Women and Infants Study (PROMOTE) placental malaria study found no difference in PTB among 356 HIV-infected gravidas randomized to receive either a PI (ritonavir-boosted lopinavir) or non-nucleoside reverse transcriptase inhibitor (efavirenz) regimen. 96…”
Section: Human Immunodeficiency Virus and Antiretroviral Therapymentioning
confidence: 99%